THE ROLE OF FISCAL POLICY IN ENSURING MACROECONOMIC STABILITY IN UZBEKISTAN (International Congress on Economics, Management and Business Studies, 2026)
This thesis provides a scientific analysis of the role and importance of fiscal policy in ensuring macroeconomic stability in Uzbekistan. The study examines key macroeconomic indicators such as gross domestic product growth, the inflation rate, the budget deficit, and public debt on the basis of the fiscal strategy designed for 2026–2028. In addition, the thesis highlights directions for strengthening economic stability through the improvement and digitalization of fiscal policy.
Keywords: macroeconomic stability, public debt, economic growth, digitalization, fiscal policy, GDP, inflation, budget deficit.